Lithium ion battery based on fused salt electrolyte

By using micron alloy material and LiFSI:KFSI molten salt electrolyte in lithium-ion batteries, combined with high-voltage positive electrode material or low-cost lithium iron phosphate positive electrode material, the problems of lithium-ion battery volume expansion, low energy density and low safety are solved, and the battery performance of high energy density, low cost and high safety is achieved.

CN119833720APending Publication Date: 2025-04-15SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510011167.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems such as volume expansion, low energy density and low safety. Especially when using micron Si anode materials, the safety of traditional liquid electrolytes is difficult to effectively solve.

Method used

A micro-alloy material is used as the negative electrode material, and a LiFSI:KFSI mixed salt with a molten salt ratio of 9:11 was combined as the LiFSI-KFSI molten salt electrolyte to construct a lithium-ion battery based on molten salt electrolyte. This battery system improves the energy density and safety of the battery by selecting high-voltage positive electrode materials or low-cost lithium iron phosphate positive electrode materials.

Benefits of technology

The high energy density, low cost, high safety and good cycle stability of lithium-ion batteries are achieved, especially in high temperature conditions, which show excellent electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a lithium ion battery based on molten salt electrolyte, which adopts a micron alloy material as a negative electrode material, and adopts LiFSI: KFSI mixed salt with the molar ratio of 9: 11 as LiFSI-KFSI molten salt electrolyte. The LiFSI-KFSI molten salt electrolyte and the micron-sized alloy negative electrode material have excellent compatibility, so that the micron-sized alloy negative electrode material shows excellent electrochemical performance in the LiFSI-KFSI molten salt electrolyte, including high initial coulombic efficiency, high capacity and long cycle life; according to the invention, one of high-Ni ternary, lithium cobalt oxide and lithium iron phosphate is selected as a positive electrode material to construct the lithium ion total battery based on the molten salt electrolyte, and the energy density of the lithium ion total battery is up to 400Wh / kg. The battery system has the advantages of high safety, excellent high-temperature characteristic, long calendar life and the like, and is a lithium ion battery with a very good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium secondary batteries, and more specifically to a lithium ion battery based on a molten salt electrolyte. Background Art

[0002] The efficient use of clean energy such as wind and solar energy is inseparable from the development and application of large-scale energy storage systems. Among the many energy storage systems, electrochemical energy storage systems are expected to be applied to large-scale energy storage due to their advantages such as high volume and mass energy density and flexible installation.

[0003] Lithium-ion batteries are widely used in daily life due to their excellent electrochemical properties, including portable electronic devices, electric vehicles and large-scale energy storage. After years of development, the energy density of lithium-ion batteries based on traditional graphite negative electrodes has now entered a bottleneck period, and its energy density is difficult to improve. The theoretical capacity of Si negative electrodes is very high, reaching 4200mAh / g, which is more than 10 times the theoretical capacity of graphite negative electrodes, and has become one of the important development directions for building the next generation of high-energy lithium-ion batteries. However, the traditional Si negative electrode has a 300% volume expansion during the lithium insertion process (lithiation), which seriously limits its application in lithium-ion batteries.

[0004] In view of the above-mentioned problem of volume expansion of silicon negative electrode, it can be summarized that there are currently four main improvement strategies to solve the problems and challenges of silicon negative electrode materials. Strategy 1: Regulation of silicon material morphology, including designing and synthesizing Si nanospheres, nanowires, etc., to inhibit the volume expansion and particle breakage of silicon materials during the cycle process; Strategy 2: Si surface coating, through carbon coating or oxide coating, reduce the contact between Si negative electrode and electrolyte, stabilize the interface between material and electrolyte, and improve electrode stability; Strategy 3: Through carbon loading, Si materials are loaded on graphite, nanocarbon tubes, and graphene substrates to improve electrode conductivity while effectively inhibiting the volume expansion of silicon electrodes; Strategy 4: Through electrolyte composition regulation, SEI is generated in situ on the surface of Si negative electrode during the electrochemical process, stabilizing the interface, inhibiting volume expansion and side reactions, and improving the electrochemical performance of Si negative electrode. However, the above-mentioned modification strategies that have been reported still have certain problems and challenges, such as the high preparation cost of nano-Si negative electrode and low electrode compaction density; the surface coating preparation process is relatively complicated; carbon-loaded Si composite materials often have low first-cycle coulomb efficiency.

[0005] Among them, strategy 4, improving the electrochemical performance of micron-Si negative electrode by modifying the electrolyte, has become the focus of research in recent years and is expected to be put into practical application. Other literature has previously reported that the stable circulation of micron-level Si negative electrode can be achieved by regulating the composition of the electrolyte. However, most of the electrolytes reported so far use ether electrolytes, including MTHF, THF, DX / DEE, etc. The flash point and boiling point of the solvents used in these ether electrolytes are generally low, which brings more serious safety problems to the battery.

[0006] Yali Liu et al. studied the MCMB anode Li4Ti5O in molten salt electrolyte. 12 The electrochemical performance of the negative electrode shows that these negative electrode materials exhibit very low first coulombic efficiency in LiFSI–KFSI molten salt electrolyte. (Electrochimica Acta 105(2013)524–529).

[0007] Minh Canh Vud et al. studied the dissolution and deposition performance of lithium metal anode in molten salt electrolyte. The results showed that the ternary molten salt electrolyte constructed by adding CsFSI salt to LiFSI-KFSI salt can effectively improve the electrochemical performance of Li metal anode. (Vu et al., Matter 6, 1–19 December 6, 2023. https: / / doi.org / 10.1016 / j.matt.2023.10.017).

[0008] Fei Xu et al. studied the electrochemical performance of natural graphite||LiFePO4 full cells in molten salt electrolyte. The decomposition of molten salt electrolyte in Li||natural graphite cells resulted in a first coulombic efficiency of 67.4%, while the first efficiency of the full cell was less than 60%. (F.Xu et al. / Electrochimica Acta 135(2014)217–223).

[0009] Zhang Shu et al. studied the electrochemical properties of LiCoO2 cathode materials in molten salt electrolytes, and the results showed that the capacity retention rate of LiCoO2 cathode materials was only 67% after 20 cycles of LiFSI-KFSI salt. (Chin. Phys. B Vol. 24, No. 7 (2015) 078201).

[0010] Ai-Min Li et al. reported a new type of symmetric electrolytes (solvent-free ionic liquids and molecular solvent) to improve the electrochemical performance of micronized Si negative electrode materials. The results showed that a LiF-rich SEI interface was formed on the surface of the Si negative electrode, thereby improving the electrochemical performance of the Si negative electrode. (Nat Energy (2024). https: / / doi.org / 10.1038 / s41560-024-01619-2 ).

[0011] Tao Liu et al. reported an ether electrolyte (3 M LiPF6 in 1,3-dioxane (DX) / 1,2-diethoxyethane (DEE) to improve the electrochemical performance of micron Si negative electrode materials. The results showed that the formation of Li2O / LiF inorganic SEI on the surface of micron Si ensured the excellent electrochemical performance of the micron Si negative electrode. (Nature Sustainability, 2024, 7(8): 1057-1066).

[0012] However, the above technology still has the following shortcomings: 1. Although the electrochemical properties of molten salt electrolytes in conventional graphite negative electrodes have been studied, the electrochemical properties of Si-based negative electrodes in LiFSI-KFSI molten salts have not been studied, especially micron-sized Si negative electrodes; 2. Although the above technology has studied the electrochemical properties of micron-sized Si negative electrodes, it is based on traditional liquid electrolytes, that is, electrolyte salts are dissolved in organic solvents. The results show that the optimization of the electrolyte improves the electrochemical properties of micron-sized Si, but the safety of traditional liquid electrolytes cannot be effectively solved; 3. The energy density of lithium-ion batteries constructed with graphite is low, which is determined by the positive and negative electrode material systems.

[0013] The reasons for the above shortcomings are: 1. The electrochemical performance of graphite anode in molten salt electrolyte is poor, which is mainly manifested in the low first coulomb efficiency, because LiFSI-KFSI molten salt is easy to reduce and decompose in graphite at high temperature to produce SEI, but LiFSI-KFSI molten salt is relatively stable on the surface of micron Si. 2. Traditional liquid electrolytes use organic solvents, which are flammable due to their intrinsic physical and chemical properties. 3. The theoretical capacity of graphite anode is only 372mAh / g, which is determined by the intrinsic physical and chemical properties of the material and cannot be adjusted. Summary of the invention

[0014] The object of the present invention is to provide a lithium-ion battery based on a molten salt electrolyte, thereby solving the problems of lithium-ion batteries in the prior art that they are prone to volume expansion, have low energy density and low safety.

[0015] In order to solve the above problems, the present invention adopts the following technical solutions:

[0016] According to the present invention, a lithium ion battery based on a molten salt electrolyte is provided. The lithium ion battery adopts a micro alloy material as a negative electrode material and adopts a LiFSI:KFSI mixed salt with a molar ratio of 9:11 as a LiFSI-KFSI molten salt electrolyte.

[0017] Preferably, the micron alloy material is one of micron Si, micron Al, micron Sn, and micron Bi. According to the present invention, in addition to micron Si-based negative electrode materials, other micron alloy materials, such as micron Al, micron Sn, and micron Bi, also exhibit excellent electrochemical properties. Among them, micron Si has the largest capacity, so it is the most preferred negative electrode material, but other micron materials, such as Al, Sn, Bi, and molten salt electrolyte combinations are also applicable to the present invention.

[0018] Preferably, the particle size of the micron alloy material is in the range of 1-20 μm. By way of example and not limitation, the particle size is about 10 μm.

[0019] Preferably, the LiFSI-KFSI molten salt electrolyte also includes other salts with a content of 0-20wt%, and the salts include at least one of LiPF6, LiBF4, KPF6, KBF4, and CsFSI.

[0020] The positive electrode material suitable for the present invention can be selected from high voltage positive electrode materials (LiNi x Co y Mn z O2, x+y+z=1), LiCoO2, or low-cost LiFePO4, where LiNi 0.8 Co 0.1 Mn 0.1 O2 has high energy density, and LiFePO4 has long cycle life and low cost.

[0021] Preferably, a slurry is prepared by mixing a micron alloy negative electrode material, a conductive agent, and a binder in a certain mass ratio, and then coated on a Cu current collector, and then dried, rolled, cut into pieces, and weighed to obtain a negative electrode; a slurry is prepared by mixing a positive electrode material, a conductive agent, and a binder in a certain mass ratio, and then coated on an Al current collector, and then dried, rolled, cut into pieces, and weighed to obtain a positive electrode.

[0022] The mass ratio of the micron alloy negative electrode material, the conductive agent and the binder is not limited to 90:5:5, but can also be 80:10:10, 70:20:10 and so on.

[0023] Preferably, the conductive agent includes: carbon black, Ketjen black ECP, conductive graphite KS-6, SFG-6, vapor grown carbon fiber VGCF, carbon nanotubes CNTs or graphene.

[0024] Preferably, the binder includes: polyvinyl alcohol, polyvinyl ketone, polymethacrylate, polyvinylidene fluoride or nano silica gel.

[0025] Preferably, the lithium-ion battery further comprises a diaphragm, and the diaphragm comprises: PP (polypropylene), glass fiber, ceramic-coated PP, PE (polyethylene), PE / PP / PE three-layer or polyimide PI to meet high temperature requirements. PP (polypropylene) diaphragm and glass fiber diaphragm are particularly preferred.

[0026] According to a preferred embodiment of the present invention, a lithium-ion battery based on a molten salt electrolyte is provided. The lithium-ion battery uses micron Si as a negative electrode material, and a slurry is prepared by mixing micron Si, a conductive agent Super P, and a binder PVDF in a mass ratio of 90:5:5, and then coating it on a Cu current collector, and then drying, rolling, cutting, and weighing to obtain a negative electrode; a LiFSI:KFSI mixed salt with a molar ratio of 9:11 is used as a LiFSI-KFSI molten salt electrolyte; LiNi 0.8 Co 0.1 Mn 0.1 O2 is the positive electrode material. 0.8 Co 0.1 Mn 0.1 O2, conductive agent Super P, and binder PVDF are mixed in a mass ratio of 90:5:5 to prepare a slurry, which is then coated on the Al current collector. After drying, rolling, cutting, and weighing, a positive electrode is obtained; a micron Si||LiNi 0.8 Co 0.1 Mn 0.1 O2 full battery, the constructed full battery can be charged and discharged in a cycle at 2.5-4.2V.

[0027] According to another preferred embodiment of the present invention, a lithium-ion battery based on a molten salt electrolyte is provided, wherein micron Si is used as a negative electrode, and a slurry is prepared by mixing micron Si, a conductive agent Super P, and a binder PVDF in a mass ratio of 90:5:5, and then coated on a Cu current collector, and a positive electrode is obtained through drying, rolling, cutting, and weighing; a LiFSI:KFSI mixed salt with a molar ratio of 9:11 is used as a LiFSI-KFSI molten salt electrolyte; LiFePO4 is used as a positive electrode material, and a slurry is prepared by mixing LiFePO4, a conductive agent Super P, and a binder PVDF in a mass ratio of 90:5:5, and then coated on an Al current collector, and a positive electrode is obtained through drying, rolling, cutting, and weighing; a micron Si||LiFePO4 full battery is constructed, and the constructed full battery can be charged and discharged in a cycle at 2.5-4.0V.

[0028] According to the present invention, the electrolyte adopts a LiFSI:KFSI electrolyte made in a molar ratio of LiFSI:KFSI=9:11. It should be understood that this molar ratio is fixed, and the melting point of the molten salt will change accordingly after the molar ratio changes. Preferably, various other salts can be further added thereto, including LiPF6, LiBF4, KPF6, KBF4, CsFSI, etc., with a content of 0-20wt%. The present invention finds that adding other salts to the LiFSI:KFSI electrolyte has the effect of regulating the melting point, physicochemical properties, redox pathways, and solid electrolyte membrane (SEI) components of the molten salt.

[0029] The present invention uses pure salt as the electrolyte, which is a mixture of LiFSI and KFSI in a certain molar ratio. The melting point of the electrolyte is about 60°C, and the lithium ion conductivity at 80°C is 2.0*10 -3 S / cm and lithium ion transfer number are 0.49. Using commercial micronized Si as the negative electrode material, the constructed Li||Si half-cell exhibits a reversible capacity of 3800mAh / g. The full-cell Si||LiNi 0.8 Co 0.1 Mn 0.1 O2 has an energy density of 400Wh / Kg and is highly safe.

[0030] In order to overcome the problems and challenges of micron silicon negative electrode materials and improve the electrochemical performance of micron silicon lithium ion batteries, the present invention screens LiFSI:KFSI molten salt electrolytes. Due to the absence of organic solvents, the reduction and decomposition of the molten salt electrolytes produce SEI that stabilizes the interface stability of the micron alloy negative electrode materials. By selecting high-voltage positive electrode materials or low-cost lithium iron phosphate positive electrodes, molten salt silicon-based lithium ion batteries are constructed. These battery systems exhibit high operating voltage, high energy density, high safety and good cycle stability. The micron alloy negative electrode lithium ion battery provided by the present invention adopts LiFSI:KFSI molten salt electrolyte, which ensures that the micron Si-based negative electrode material exhibits good electrochemical performance. The constructed micron alloy negative electrode material lithium ion battery has the advantages of high energy density, low cost, high safety, etc., and the battery maintains a very high storage life at room temperature.

[0001] The key invention of the present invention is that a molten salt electrolyte is used to make micron Si and other micron alloy negative electrode materials have good electrochemical properties. A lithium-ion battery based on molten salt electrolyte is constructed by selecting a high Ni ternary (Ni content greater than 60%) positive electrode material, lithium cobalt oxide, and lithium iron phosphate as the positive electrode material. Micron-sized alloy negative electrode materials are used in LiFSI-KFSI molten salt electrolytes. Since LiFSI-KFSI molten salt electrolytes have good compatibility with micron-sized alloy negative electrode materials, micron-sized alloy negative electrode materials exhibit excellent electrochemical properties in LiFSI-KFSI molten salt electrolytes, including high first coulomb efficiency, high capacity, and long cycle.

[0031] Compared with the prior art, the present invention has the following advantages: the present invention adopts micron alloy negative electrode material, which is low-cost and easy to prepare; the lithium ion battery constructed by the present invention has a high energy density; the lithium ion battery constructed by the present invention has excellent electrochemical properties at high temperatures (greater than 80°C); the micron alloy negative electrode material adopted by the present invention has good cycle stability; the lithium ion battery constructed by the present invention using the micron alloy negative electrode material has low self-discharge and excellent storage life; in addition to micron Si-based negative electrode materials, other micron alloy materials, including Al, Sn, etc., also show excellent electrochemical properties.

[0032] In summary, according to the present invention, a lithium-ion battery based on a molten salt electrolyte is disclosed, wherein the lithium-ion battery uses a micron alloy material as a negative electrode material, and uses a LiFSI:KFSI mixed salt with a molar ratio of 9:11 as a LiFSI-KFSI molten salt electrolyte. Since the LiFSI-KFSI molten salt electrolyte has good compatibility with the micron-sized alloy negative electrode material, the micron alloy negative electrode material exhibits excellent electrochemical properties in the LiFSI-KFSI molten salt electrolyte, including high first coulomb efficiency, high capacity, and long cycle life. The present invention also selects one of a high Ni ternary positive electrode material, lithium cobalt oxide, and lithium iron phosphate as a positive electrode material to construct a lithium-ion full battery based on a molten salt electrolyte. The energy density of the lithium-ion battery constructed according to the present invention is as high as 400Wh / kg. In addition, the battery system has the advantages of high safety, excellent high temperature characteristics, and long calendar life, and is a lithium-ion battery with great application prospects. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with specific examples. It should be understood that the following examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional operations in the art, or according to the experimental methods recommended by the instrument and equipment manufacturers. The reagents and materials used in the examples can be obtained from commercial sources unless otherwise specified.

[0034] Embodiment 1:

[0035] Commercial micronized Si with a particle size of about 10 μm was used as the negative electrode material. Micronized Si, conductive agent Super P, and binder PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Cu current collector. After drying, rolling, cutting, and weighing, the negative electrode was obtained. The electrode loading was 0.5 mg / cm 2 (Range 0.5-2.0mg / cm 2 ). The electrolyte uses a LiFSI:KFSI mixed salt with a molar ratio of 9:11. The battery assembly is carried out in a glove box (water and oxygen values ​​are less than 0.5ppm), and the temperature is maintained at 80°C during assembly (the range can be 80-150°C). The mass of the molten salt electrolyte is 150mg (80-150mg). The diaphragm uses a polypropylene PP diaphragm (modified PE, modified PP, PI, glass fiber, etc.). It is assembled into a Li||Si battery and cycled at 80°C. Its electrochemical properties are shown in Table 1, including the first coulomb efficiency, reversible capacity, and cycle life.

[0036] Embodiment 2:

[0037] Commercial micronized Al with a particle size of about 10 μm was used as the negative electrode material. Micronized Al, conductive agent Super P, and binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Cu current collector. After drying, rolling, cutting, and weighing, the negative electrode was obtained. The electrode loading was 0.5 mg / cm 2 (Range 0.5-2.0mg / cm 2 ). The electrolyte uses a LiFSI:KFSI mixed salt with a molar ratio of 9:11 (various other salts can also be added to it, including LiPF6, LiBF4, KPF6, KBF4, CsFSI, etc., with a content of 0-20wt%). The battery assembly is carried out in a glove box (water and oxygen values ​​are less than 0.5ppm), and the temperature is maintained at 80°C during assembly (the range can be 80-150°C). The mass of the molten salt electrolyte is 150mg (80-150mg). The diaphragm uses a polypropylene PP diaphragm (modified PE, modified PP, PI, glass fiber, etc.). Assemble into a Li||Al battery and cycle at 80°C. Its electrochemical properties are shown in Table 1, including the first coulomb efficiency, reversible capacity, and cycle life.

[0038] The only difference between Example 2 and Example 1 is that micron Al is used instead of micron Si, which proves that in the molten salt electrolyte, not only micron Si but also micron Al negative electrode can show good electrochemical performance.

[0039] Embodiment 3:

[0040] Commercial micronized Si with a particle size of about 10 μm was used as the negative electrode material. Micronized Si, conductive agent Super P, and binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Cu current collector. After drying, rolling, cutting, and weighing, the negative electrode was obtained. The electrode loading was 0.5 mg / cm 2 (Range 0.5-2.0mg / cm 2 ). The electrolyte uses a LiFSI:KFSI mixed salt with a molar ratio of 9:11, and 10wt% CsFSI is added. The battery assembly is carried out in a glove box (water and oxygen values ​​are less than 0.5ppm), and the temperature is maintained at 80°C during assembly (the range can be 80-150°C). The mass of the molten salt electrolyte is 150 (80-150mg). The diaphragm uses a PP diaphragm (modified PE, modified PP, PI, glass fiber, etc. are acceptable). It is assembled into a Li||Si battery and cycled at 80°C. Its electrochemical properties are shown in Table 1, including the first coulomb efficiency, reversible capacity, and cycle life.

[0041] The only difference between Example 3 and Example 1 is that 10 wt% CsFSI is added to the LiFSI:KFSI electrolyte with a molar ratio of 9:11. The effect comparison shows that the addition of CsFSI can improve the cycle stability of the Si negative electrode, thereby improving the electrochemical performance of the battery.

[0042] Embodiment 4:

[0043] Commercial micronized Si with a particle size of about 10 μm was used as the negative electrode material. Micronized Si, conductive agent Super P, and binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Cu current collector. After drying, rolling, cutting, and weighing, the negative electrode was obtained. The electrode loading was 0.5 mg / cm 2 (Range 0.5-2.0mg / cm 2 ). The electrolyte uses a mixed salt of LiFSI:KFSI (the molar ratio is 9:11, and various other salts can be added here, including LiPF6, LiBF4, KPF6, KBF4, CsFSI, etc., with a content of 0-20%, mass ratio). The battery assembly is carried out in a glove box (water and oxygen values ​​are less than 0.5ppm), and the temperature is maintained at 80°C during assembly (the range can be 80-150°C). The mass of the molten salt electrolyte is 150mg (80-150mg). The diaphragm uses a glass fiber diaphragm (modified PE, modified PP, PI, etc. are acceptable). It is assembled into a Li||Si battery and cycled at 80°C. Its electrochemical properties are shown in Table 1, including the first coulomb efficiency, reversible capacity, and cycle life.

[0044] The difference between Example 4 and Example 1 is that a glass fiber separator is used instead of a PP separator. The effect comparison shows that there are multiple choices for the separator of the battery, and the separator has little effect on the battery performance. In addition, the glass fiber separator has a higher operating temperature.

[0045] Embodiment 5:

[0046] Commercial micronized Si with a particle size of about 10 μm was used as the negative electrode material. Micronized Si, conductive agent Super P, and binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Cu current collector. After drying, rolling, cutting, and weighing, the negative electrode was obtained. The electrode loading was 0.5 mg / cm 2 (Range 0.5-2.0mg / cm 2). The electrolyte uses a mixed salt of LiFSI:KFSI with a molar ratio of 9:11. The battery assembly is carried out in a glove box (water and oxygen values ​​are less than 0.5ppm), and the temperature is maintained at 80°C during assembly. The mass of the molten salt electrolyte is 150mg. The diaphragm uses a glass fiber diaphragm. It is assembled into a Li||Si battery and cycled at 100°C. Its electrochemical properties are shown in Table 1, including the first coulombic efficiency, reversible capacity, and cycle life.

[0047] The only difference between Example 5 and Example 1 is that a cycle temperature of 100°C is used. The effect comparison shows that by using a glass fiber separator, the operating temperature of the battery can reach 100°C, and the battery still exhibits good electrochemical properties at a temperature of 100°C.

[0048] It should be understood that Examples 1-5 are mainly concerned with the negative electrode, which illustrates that negative electrode materials such as micron Si can exhibit good performance in molten salt electrolytes.

[0049] Examples 6-7 respectively use LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiFePO4 are positive electrode materials, which are combined with negative electrode materials such as micron Si verified above to build a battery.

[0050] Embodiment 6:

[0051] Commercial micronized Si with a particle size of about 10 μm was used as the negative electrode material. Micronized Si, conductive agent Super P, and binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Cu current collector. After drying, rolling, cutting, and weighing, the negative electrode was obtained. The electrode loading was 0.5 mg / cm 2 (Range 0.5-2.0mg / cm 2 ). The electrolyte uses a LiFSI:KFSI mixed salt with a molar ratio of 9:11. 0.8 Co 0.1 Mn 0.1 O2 is the positive electrode material, the conductive agent Super P, and the binder PVDF are mixed in a mass ratio of 90:5:5 to prepare a slurry, which is then coated on the Al current collector. After drying, rolling, cutting, and weighing, the positive electrode is obtained. 0.8 Co 0.1 Mn 0.1 O2 full battery. The constructed battery can be charged and discharged at 2.5-4.2V. Its electrochemical performance is shown in Table 1, including the first coulombic efficiency, reversible capacity, and cycle life.

[0052] In this embodiment, micron Si negative electrode and positive electrode material LiNi0.8 Co 0.1 Mn 0.1 O2 builds a complete battery.

[0053] Embodiment 7:

[0054] Commercial micronized Si with a particle size of about 10 μm was used as the negative electrode material. Micronized Si, conductive agent Super P, and binder PVDF were mixed in a mass ratio of 90:5:5 to prepare a slurry, which was then coated on the Cu current collector. After drying, rolling, cutting, and weighing, the negative electrode was obtained. The electrode loading was 0.5 mg / cm 2 (Range 0.5-2.0mg / cm 2 ). The electrolyte uses a mixed salt of LiFSI:KFSI with a molar ratio of 9:11. LiFePO4 is used as the positive electrode material, and the conductive agent Super P and the binder PVDF are mixed in a mass ratio of 90:5:5 to prepare a slurry, which is then coated on the Al current collector. After drying, rolling, cutting and weighing, the positive electrode is obtained. Construct a micron Si||LiFePO4 full battery. The constructed battery can be charged and discharged at 2.5-4.0V. Its electrochemical properties are shown in Table 1, including the first coulomb efficiency, reversible capacity, and cycle life.

[0055] In this embodiment, a complete battery is constructed by using micron Si negative electrode and positive electrode material LiFePO4. The difference between Example 7 and Example 6 is that LiFePO4 is used instead of LiNi 0.8 Co 0.1 Mn 0.1 O2. Among them, LiNi 0.8 Co 0.1 Mn 0.1 O2 batteries have high energy density and are more suitable for power batteries, especially for electric vehicles. LiFePO4 batteries have long cycle life and low cost, making them suitable for large-scale energy storage.

[0056] Table 1: Electrochemical performance of lithium-ion batteries using different negative electrodes, electrolytes, positive electrodes, and separators

[0057] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention. The above embodiments of the present invention can also be modified in various ways. All simple, equivalent changes and modifications made according to the claims and the description of the present invention fall within the scope of protection of the claims of the present invention. The contents not described in detail in the present invention are all conventional technical contents.

Claims

1. A lithium-ion battery based on molten salt electrolyte, characterized in that: The lithium-ion battery uses a micron alloy material as the negative electrode material and a LiFSI:KFSI mixed salt with a molar ratio of 9:11 as the LiFSI-KFSI molten salt electrolyte.

2. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The micron alloy material is one of micron Si, micron Al, micron Sn and micron Bi.

3. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The particle size of the micron alloy material is in the range of 1-20 μm.

4. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The LiFSI-KFSI molten salt electrolyte also includes other salts with a content of 0-20wt%, and the salts include at least one of LiPF6, LiBF4, KPF6, KBF4, and CsFSI.

5. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The lithium ion battery adopts LiNi x Co y Mn z Any one of O2 (x+y+z=1), LiFePO4 or LiCoO2 is the positive electrode material.

6. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The slurry is prepared by mixing a micron alloy negative electrode material, a conductive agent, and a binder in a certain mass ratio, and then coated on a Cu current collector, and then dried, rolled, cut into pieces, and weighed to obtain a negative electrode; the slurry is prepared by mixing a positive electrode material, a conductive agent, and a binder in a certain mass ratio, and then coated on an Al current collector, and then dried, rolled, cut into pieces, and weighed to obtain a positive electrode.

7. The lithium-ion battery based on molten salt electrolyte according to claim 6, characterized in that: The conductive agent includes: carbon black, Ketjen black ECP, conductive graphite KS-6, SFG-6, vapor-grown carbon fiber VGCF, carbon nanotubes CNTs or graphene; the binder includes: polyvinyl alcohol, polyvinyl ketone, polymethacrylate, polyvinylidene fluoride or nano silica gel.

8. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The lithium-ion battery further comprises a separator, which comprises: PP, glass fiber, ceramic-coated PP, PE, PE / PP / PE three layers or polyimide PI.

9. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The lithium-ion battery uses micron Si as the negative electrode material. The slurry is prepared by mixing micron Si, conductive agent Super P, and binder PVDF in a mass ratio of 90:5:5, and then coated on the Cu current collector. The negative electrode is obtained by drying, rolling, cutting, and weighing. The LiFSI:KFSI mixed salt with a molar ratio of 9:11 is used as the LiFSI-KFSI molten salt electrolyte; LiNi 0.8 Co 0.1 Mn 0.1 O2 is the positive electrode material. 0.8 Co 0.1 Mn 0.1 O2, conductive agent Super P, and binder PVDF are mixed in a mass ratio of 90:5:5 to prepare a slurry, which is then coated on the Al current collector. After drying, rolling, cutting, and weighing, a positive electrode is obtained; a micron Si||LiNi 0.8 Co 0.1 Mn 0.1 O2 full battery, the constructed full battery can be charged and discharged in a cycle at 2.5-4.2V.

10. The lithium-ion battery based on molten salt electrolyte according to claim 1, characterized in that: The lithium-ion battery uses micron Si as the negative electrode, and the slurry is prepared by mixing the micron Si, conductive agent Super P, and binder PVDF in a mass ratio of 90:5:5, and then coated on a Cu current collector, and the negative electrode is obtained through drying, rolling, cutting, and weighing; a LiFSI:KFSI mixed salt with a molar ratio of 9:11 is used as the LiFSI-KFSI molten salt electrolyte; LiFePO4 is used as the positive electrode material, and the slurry is prepared by mixing LiFePO4, conductive agent Super P, and binder PVDF in a mass ratio of 90:5:5, and then coated on an Al current collector, and the positive electrode is obtained through drying, rolling, cutting, and weighing; a micron Si||LiFePO4 full battery is constructed, and the constructed full battery can be charged and discharged in a cycle at 2.5-4.0V.

Citation Information

Cited By

  • Molten salt lithium battery

    CN120834298A